PENGARUH PENGANGGARAN PARTISIPATIF, KEJELASAN SASARAN ANGGARAN TERHADAP KINERJA MANAJERIAL PEMERINTAH KABUPATEN ACEH UTARA - Muzahid, Mukhlisul (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2017)
This study aims to test empirically the effects of participatory budgeting, budget goalclarity either simultaneously or partially on the managerial performance of localgovernment in North Aceh District. The analysis tool is multiple regression analysistechnique to measure how much the effect of participatory budgeting, budget goalclarity simultaneously and partially on managerial performance in North AcehDistrict. Respondents are 32 respondents, because it is believed that they have awide access in processing of budget. The source of the data are primary datathrough questionnaires and interviews. The results of this study have showed thatparticipatory budgeting and budget goal clarity effect on managerial performancesimultaneous, and participatory budgeting and budget goal clarity positive effect onmanagerial performance of the district government partially. The results haveexpected to be a reference and consideration for local governments, especially thedistrict that participatory budgeting and budget goal clarity can be applied in thebudgeting process.